Descomposición del mantillo del árbol del caucho Hevea brasiliensis en dos profundidades - Gréggio, Thiago Claudino [UNESP]; Assis, Luiz Carlos [UNESP]; Nahas, Ely [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2008)
The decomposition of soil litter contributes to maintaining agricultural sustainability, since the nutrients released by microbial activity are determinants of the net productivity of the agroecosystem. The decomposition of rubber tree (Hevea brasiliensis [Willd. ex A. Juss.] Müll. Arg.) leaves located on the surface and buried in at 10 cm depth in Forest and Savannah (Cerradão) soils (Oxisols) was studied, with emphasis on the production of CO2 and the monthly variation of the remaining amounts of litter mass, soluble substances, cellulose and lignin. To evaluate CO2 production, H. brasiliensis leaves were incubated for 30 days in soils from the 0-2 cm and 10-12 cm layers. CO2 production increased in the 0-2 cm layer in comparison to the 10-12 cm layer. Litter mass and soluble substance loss was of 62 and 72% at the end of nine months of incubation, and of 38 and 65%, respectively, in the first three months, being greater in the deeper (71-74%) than in surface layer (48-55%). Forest soil stimulated more litter mass loss and cellulose decomposition (only in the surface layer) than Savannah soil. The cellulose (25%) content decreased and lignin (30%) increased in the initial months of incubation, however, at the end of the period of this study the same content (29%) was found.
Decomposition of the rubber tree hevea brasiliensis litter at two depths
Keywords: Cellulose; Lignin; Litter mass; Litter-bags; Soluble substances